A selective complexing leaching process for deep removal of zirconium from electronic grade titanium dioxide
Patent Information
- Application Number
- CN202611234954.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-23
AI Technical Summary
[0008]本发明的目的在于提供一种电子级二氧化钛深度除锆的选择性络合浸出工艺,可以有效解决现有技术中二氧化钛除锆效率低、钛损失率高、工艺复杂以及适用范围有限的问题
[0029]1.深度除锆能力强:本发明通过选择性络合浸出工艺,可将含锆0.1 wt%至5 wt%的二氧化钛原料中的锆含量降至0.05 wt%以下,除锆效率显著优于现有水洗除杂工艺,满足电子级二氧化钛对锆含量的严格要求。
Smart Images

Figure CN122959540A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of hydrometallurgy, specifically relating to a selective complexation leaching process for deep zirconium removal from electronic-grade titanium dioxide. Background Technology
[0002] Electronic-grade titanium dioxide, as an important inorganic non-metallic functional material, has been widely used in strategic emerging industries such as electronic ceramics, photocatalysis, sensors, and high-end coatings due to its excellent dielectric properties, photoelectric conversion characteristics, and chemical stability. With the rapid development of downstream fields such as 5G communication, new energy vehicles, and smart terminals, the market has placed more stringent requirements on the purity of electronic-grade titanium dioxide. In particular, the control of the content of key associated impurities such as zirconium, iron, and silicon has become a core technological barrier determining product quality. Zirconium, as one of the most abundant elements in the Earth's crust, is commonly found associated with titanium in major titanium resources such as ilmenite and rutile. Its chemical properties are highly similar to titanium, making complete separation difficult during the sulfuric acid or chloride process for titanium dioxide production, which is one of the key bottlenecks restricting the improvement of the purity of electronic-grade titanium dioxide products. The presence of zirconium impurities significantly alters the lattice constant, dielectric constant, and band structure of materials, thereby affecting the consistency, reliability, and service life of electronic components. Therefore, developing efficient deep zirconium removal technology for titanium dioxide has significant industrial application value and economic significance.
[0003] To gain a comprehensive understanding of the current state of technological development, this application systematically searched and analyzed relevant patents and non-patent literature concerning zirconium removal processes in titanium dioxide, both domestically and internationally. The search scope covered the China National Patent Database (CNPAT), the Derwent World Patent Index (DWPI), Chemical Abstracts (CA), and the Web of Science Core Collection. Keywords included "titanium dioxide / titanium white / titanium oxide," "zirconium removal / zirconium stripping," "leaching / wet leaching / selective leaching," "complexation / coordination," "fluorine / fluoride ions," and their synonyms and combinations. The search period ended before the application date. The search results show that current research on zirconium impurity removal processes in titanium dioxide, both domestically and internationally, mainly focuses on the following technological directions:
[0004] (1) Acid-water washing method based on hydrated titanium dioxide intermediates. For example, the technical solution with publication number CN120350251B adopts the hydrated titanium dioxide intermediate route. Through acid-water washing, secondary hydrolysis and multiple fine washing operations, the synergistic removal of multiple impurity elements such as iron, phosphorus, niobium and zirconium is achieved, and the purity of the obtained product can reach more than 99.9%. This method mainly focuses on the whole-process impurity removal from the ilmenite raw material end. The process route involves multiple processes such as acid-water washing, precipitation, hydrolysis and calcination. The process control is complicated and the production cost is high. More importantly, this method uses multiple water washing to remove impurities. Its impurity removal mechanism mainly relies on the physical washing to remove soluble impurities. However, for zirconium impurities that exist in the form of oxides or composite minerals inside the titanium dioxide lattice or particles, the water washing process can hardly achieve effective removal. Therefore, for electronic-grade applications where the zirconium content needs to be less than 0.05 wt%, the deep zirconium removal capability of this method is obviously insufficient. Furthermore, frequent washing operations can lead to the loss of a large number of ultrafine titanium dioxide particles with the washing liquid, resulting in a significant titanium loss rate and affecting the overall product yield. More importantly, this method is designed for the entire processing of ilmenite raw materials and is a front-end impurity removal process. It is not suitable for the process requirements of deep zirconium removal and purification of already prepared titanium dioxide products, thus its application scenarios are clearly limited.
[0005] (2) Pyrometallurgical process based on high-temperature melting-halogenation volatilization. For example, the technical solution with publication number CN1594104A mixes zircon sand and carbon reducing agent and melts them at high temperature in an electric arc furnace to remove silicon. It uses the principle of chemical reaction between halides and impurity components to generate gas that escapes to prepare high-purity zirconium dioxide. The target product of this technology is high-purity zirconium dioxide. Its core is to retain zirconium while removing other impurities such as silicon and iron, which is completely opposite to the technical objective of this invention—deep removal of zirconium impurities from titanium dioxide. From the perspective of process principle, pyrometallurgical melting process requires high-temperature operation above 2000℃ in an electric arc furnace, which consumes a lot of energy. Moreover, under high-temperature conditions, halides severely corrode the furnace lining material, and the requirements for equipment materials are extremely strict. It should also be noted that this process removes impurities through high-temperature volatilization. During this process, the titanium dioxide matrix may also volatilize or undergo phase transformation, resulting in damage to the product's phase structure. Simultaneously, under high-temperature conditions, other metallic impurities (such as chromium, nickel, and vanadium) from the furnace lining, electrodes, or raw materials may be reduced and enter the product, introducing new contamination and affecting the final purity. The high energy consumption, high equipment investment, and risk of secondary impurity introduction in this type of pyrometallurgical process make it completely unsuitable for the deep zirconium removal requirements of electronic-grade titanium dioxide.
[0006] (3) Methods based on direct acid leaching with hydrofluoric acid or fluorides. Relevant literature reports on the use of hydrofluoric acid (HF) or ammonium fluoride combined with sulfuric acid to remove impurities from titanium dioxide. This type of method utilizes the complexation and dissolution effect of fluoride ions on zirconium to achieve zirconium removal. However, the existing methods generally have the following prominent problems: First, when the concentration of hydrofluoric acid is too high or the acidity of sulfuric acid is too strong, the solubility of titanium dioxide matrix in fluorine-containing systems increases significantly, and the titanium loss rate is often as high as 10% to 20%, which seriously affects the product yield; Second, high concentrations of hydrofluoric acid are extremely corrosive and toxic, and the risk of HF gas escape during operation is high, posing a serious threat to the safety of operators and the environment, which greatly limits industrial application; Third, existing reports lack systematic optimization of the matching relationship of process parameters such as fluoride ion concentration, acidity, and temperature. Usually, only the influence of a single factor on the zirconium removal rate is considered, and the multi-dimensional indicators such as titanium recovery rate, operational safety, and economy are not taken into account, making it difficult to realize the industrial transformation of related technical solutions.
[0007] In summary, the existing technologies described above demonstrate that current titanium dioxide methods for zirconium removal still have significant shortcomings in terms of deep zirconium removal efficiency, process simplicity, titanium loss rate, environmental friendliness, and applicability. Specifically, water washing cannot destroy the solid-phase mineral structure of zirconium impurities, pyrometallurgical processes have high energy consumption and secondary pollution risks, while traditional hydrofluoric acid leaching faces the dual dilemmas of excessive dissolution of the titanium matrix and operational safety. None of these methods address the fundamental principle of the difference in complexation chemistry between zirconium and titanium in fluorinated sulfuric acid systems, and fail to achieve efficient targeted separation of zirconium through selective coordination design. There is an urgent need to develop a novel deep zirconium removal process that can achieve efficient and selective removal of zirconium impurities under mild operating conditions while minimizing titanium matrix loss. Summary of the Invention
[0008] The purpose of this invention is to provide a selective complexation leaching process for deep zirconium removal from electronic-grade titanium dioxide, which can effectively solve the problems of low zirconium removal efficiency, high titanium loss rate, complex process and limited applicability in the prior art.
[0009] To achieve the above objectives, the technical solution adopted by this invention is as follows: a selective complexation leaching process for deep zirconium removal from electronic-grade titanium dioxide, comprising the following specific steps: Step 1: Pretreatment of zirconium-containing titanium dioxide raw material: The zirconium-containing titanium dioxide raw material is crushed and ground to a predetermined particle size range, wherein the zirconium content is 0.1 wt% to 5 wt%, and the particle size D50 is 0.5 to 10 μm; Step 2: Preparation of selective leaching agent: Fluoride ion source and sulfuric acid are mixed in water to prepare the leaching agent, wherein the total concentration of fluoride ions is 0.5 to 3 mol / L, and the concentration of sulfuric acid is 1 to 4 mol / L; Step 3: Selective complexation leaching: The pretreated titanium dioxide powder and the leaching agent are added to a reaction vessel at a liquid-solid mass ratio of 3:1 to 10:1, and the leaching reaction is carried out at 50 to 95°C for 0.5 to 5 hours under stirring conditions, so that zirconium and fluoride ions form soluble fluorine-zirconium complex ions that enter the liquid phase, while the titanium dioxide matrix remains in a solid phase.
[0010] The method for determining the reaction endpoint is as follows:
[0011] Zirconium concentration method in filtrate (preferred): Approximately 5 mL of slurry sample is taken from the sampling port of the reactor every 30 minutes. After filtration through a 0.45 μm filter membrane, the Zr concentration in the filtrate is determined using inductively coupled plasma optical emission spectrometry (ICP-OES). The leaching endpoint is defined as the difference between two consecutive measurements of zirconium concentration in the filtrate being <5% and the zirconium concentration in the filtrate being <50 mg / L. It should be noted that this 50 mg / L threshold is applicable to conventional operating conditions with an initial zirconium content of 0.1–5 wt% and a liquid-to-solid ratio of 3:1–10:1. When the liquid-to-solid ratio is high (e.g., >8:1) or the initial zirconium content is low (<0.5 wt%), the endpoint zirconium concentration in the filtrate can be correspondingly relaxed to <80 mg / L, specifically based on a difference between two consecutive measurements of <5% and a stable zirconium concentration in the filtrate. Those skilled in the art can make adaptive adjustments according to actual operating conditions.
[0012] (2) pH value method (auxiliary): Monitor the pH value change of the slurry in the reactor. When the pH value tends to stabilize (change rate < 0.1 pH unit / 10 minutes) and is close to the initial pH value (±0.3), it indicates that the zirconium has been basically leached.
[0013] (3) Dynamic adjustment logic: When the initial zirconium content of the raw material is ≥3 wt% or D50>5 μm, the leaching time is extended to 2.5~5 hours, and the temperature is maintained in the range of 75~85℃; when the zirconium content is <1 wt% and D50<2 μm, the leaching time can be shortened to 0.5~1.5 hours. When the filtrate zirconium concentration method is used to determine the endpoint, the actual leaching time is based on the arrival of the endpoint, and the time window is only used as a reference range.
[0014] Step 4: Solid-liquid separation and product preparation: The slurry after leaching is subjected to solid-liquid separation. The resulting filter cake is washed with deionized water until the pH of the washing solution is close to neutral. The filter cake is then dried at 100 to 150°C to obtain a low-zirconium titanium dioxide product. Step 5: Leachate treatment and recycling: An alkaline substance is added to the leachate after solid-liquid separation to adjust the pH to 8 to 10, causing zirconium and residual impurities to precipitate. The supernatant is adjusted in composition and returned to be used to prepare the leaching agent. The performance maintenance method for recycling is as follows:
[0015] (1) Batch Circulation Control: The leaching agent can be recycled for 5-10 batches, with the specific number of cycles depending on the impurity content in the raw material. When Fe is detected in the supernatant... 3+ Concentration >2 g / L, Al 3+ Concentration >1 g / L or Ca 2+ When the concentration is >3 g / L, a portion of the leaching agent (not less than 20% of the total amount) should be discharged and replaced with freshly prepared leaching agent to maintain the selectivity of the system.
[0016] (2) Fluoride ion concentration maintenance: Before each batch cycle, free F is measured by an online fluoride ion selective electrode. - Concentration. When free F - When the concentration is below 80% of the initial value, add a calculated amount of fluorosilicic acid or ammonium bifluoride to bring it back to the original concentration level. The amount added is calculated as Δ[F]. - ] × Calculation of total amount of leachate.
[0017] (3) Impurity removal method: When the accumulation of impurity ions leads to a decrease in selectivity, lime milk (Ca(OH)2 concentration 10~15 wt%) is used to adjust the pH to 10~11, so that Fe 3+ Al 3+ Removed by the formation of hydroxide precipitate, Ca 2+ The sample was separated by precipitation in the form of calcium sulfate; after precipitation, the supernatant was replenished with a fluoride ion source and sulfuric acid to restore it to its original composition.
[0018] (4) Judgment of the end point of recycling: When the titanium recovery rate of two consecutive batches of products is less than 97% or the zirconium content is higher than 0.06 wt%, recycling should be stopped and the leaching agent should be regenerated or completely replaced.
[0019] Preferably, the fluoride ion source is at least one of fluorosilicic acid, ammonium bifluoride, ammonium fluoride, and sodium fluoride. When fluorosilicic acid is used as the fluoride ion source, the introduced silicate ions can form co-precipitates with zirconium in the subsequent neutralization and precipitation process, which facilitates the comprehensive recovery of zirconium and silicon and significantly improves the economic efficiency and resource utilization of the process.
[0020] Preferably, the fluoride ion source is a mixture of fluorosilicic acid and ammonium bifluoride, with a molar ratio of 1:0.5 to 2. Within this ratio range, a stable hexafluorozirconium complex ion can be formed while maintaining a low free fluoride ion concentration. This ensures efficient leaching of zirconium and effectively inhibits excessive dissolution of the titanium dioxide matrix, thus achieving the goal of selective zirconium removal.
[0021] Preferably, in step 2, the sulfuric acid concentration is 2 to 3 mol / L and the total fluoride ion concentration is 1 to 2 mol / L. Within this concentration range, the leaching rate of zirconium reaches the optimal value, and the dissolution loss of titanium dioxide under this condition can be controlled within 1.5%, thus taking into account both the zirconium removal efficiency and titanium recovery rate, two key indicators.
[0022] Preferably, the leaching temperature in step 3 is controlled at 70 to 85°C and the leaching time is 1 to 2.5 hours. Within this temperature and time range, the corrosive effect of sulfuric acid on the titanium matrix is weak, and fluoride ions mainly exist in the form of complexes rather than volatilize and be lost in the form of hydrogen fluoride, which ensures both reaction efficiency and operational safety and process stability.
[0023] Preferably, the original zirconium content of the zirconium-containing titanium dioxide raw material in step 3 is 0.1 wt% to 5 wt%, and the raw material particle size D50 is 0.5 to 10 μm. After fine grinding, the specific surface area of the raw material is increased, which is conducive to the full contact and reaction mass transfer between the leaching agent and the zirconium impurities, thereby improving the zirconium removal efficiency and reaction uniformity.
[0024] Preferably, in step 4, deionized water is used for the washing process, the washing temperature is 60 to 80°C, and the washing is carried out until the pH value of the filter cake washing liquid reaches the range of 6.5 to 7.5 before drying. This operation can effectively remove residual sulfate and fluoride ions in the filter cake and avoid the formation of insoluble salts during the drying process, which would affect the purity of the product.
[0025] Preferably, the alkaline substance added in step 5 is any one of lime milk, sodium hydroxide, or calcium hydroxide. When the pH is adjusted to 8.5 to 9.5, the precipitation rate of zirconium can reach more than 95%. After pressure filtration and drying, the precipitated product can be sold or further processed as zirconium silicon slag, realizing the resource utilization of by-products.
[0026] The present invention further provides a low-zirconium titanium dioxide product, which is prepared by the above-mentioned selective complexation leaching process. The zirconium content of the low-zirconium titanium dioxide product is less than 0.05 wt%, the titanium recovery rate is greater than 98.5%, and the purity of the product meets the high-end application requirements of electronic-grade titanium dioxide. It can be widely used in strategic emerging industries such as electronic ceramics, photocatalysis, and sensors.
[0027] The reaction mechanism of this invention is based on the difference in complexation chemistry between zirconium and titanium in a fluorinated sulfuric acid system. In sulfuric acid, zirconium first forms zirconium oxysulfate. However, in the presence of fluoride ions, tetravalent zirconium ions preferentially coordinate with fluoride ions to form stable complexes such as zirconium hexafluorophosphate, whose stability constant is much higher than that of zirconium-sulfate complexes, thus significantly accelerating the dissolution of solid zirconium. Meanwhile, titanium dioxide has extremely low solubility in 1 to 4 mol / L sulfuric acid, and the stability of the complexes formed by titanium and fluoride ions is much weaker than that of zirconium-fluoride complexes. At the same time, the presence of high-concentration sulfuric acid inhibits the amphoteric dissolution tendency of titanium dioxide. By precisely controlling the process parameters of fluoride ion concentration, sulfuric acid concentration, and temperature, the goal of highly selective leaching of zirconium is achieved while the titanium dioxide matrix hardly participates in the reaction is realized.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. Strong deep zirconium removal capability: This invention uses a selective complexation leaching process to reduce the zirconium content in titanium dioxide raw materials containing 0.1 wt% to 5 wt% zirconium to below 0.05 wt%. The zirconium removal efficiency is significantly better than the existing water washing and impurity removal process, meeting the strict requirements of electronic-grade titanium dioxide for zirconium content.
[0030] 2. High titanium recovery rate: Using the selective complexation system of this invention, the dissolution loss of titanium is controlled within the range of 0.5% to 2%, which is far lower than the titanium loss rate of 10% to 20% in the direct hydrofluoric acid leaching process. The titanium recovery rate can reach more than 98.5%, effectively ensuring product yield and economic benefits.
[0031] 3. Mild process conditions: The present invention can complete the zirconium removal operation under mild conditions of normal pressure and 50 to 95°C, without the need for high temperature and high pressure equipment. The process operation is simple and safe, and the requirements for equipment materials are relatively low, which reduces equipment investment and operating costs.
[0032] 4. Environmentally friendly: This invention does not use high-concentration hydrofluoric acid as a leaching agent. Fluorosilicic acid and sulfuric acid have low volatility and toxicity. The leaching solution can be recycled for the preparation of leaching agents after neutralization and precipitation treatment, which greatly reduces the amount of waste liquid discharged and reagent consumption, and meets the development requirements of green chemistry and clean production.
[0033] 5. Wide range of applications: This invention has a good zirconium removal effect on a variety of raw materials, such as the calcined products of metatitanic acid from the sulfuric acid process, the dust collected in the oxidation stage of the chloride process, and titanium dioxide enriched by titanium slag. It is not only suitable for the deep zirconium removal process of newly built production lines, but also for the upgrading and transformation of existing titanium dioxide production lines, with broad application prospects. Attached Figure Description
[0034] Figure 1 This is a schematic diagram of the overall process flow of a selective complexation leaching process for deep zirconium removal from electronic-grade titanium dioxide according to an embodiment of this application.
[0035] Figure 2 This is a schematic diagram of the core principle framework of the selective complexation leaching process according to the embodiments of this application. Detailed Implementation
[0036] like Figure 1 As shown, the process of this invention mainly includes five core modules: raw material pretreatment, leaching agent preparation, selective complexation leaching, solid-liquid separation and product preparation, and leachate recycling. Figure 2 Further, from a chemical principle perspective, the mechanism of the difference in complexation selectivity between zirconium and titanium in fluorinated sulfuric acid systems was demonstrated.
[0037] Example 1
[0038] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.
[0039] This invention provides a selective complexation leaching process for deep zirconium removal from electronic-grade titanium dioxide. The overall technical solution comprises five core steps: raw material pretreatment, selective leaching agent preparation, selective complexation leaching, solid-liquid separation and product preparation, and leachate treatment and recycling. The technical implementation details of each step are as follows.
[0040] Step 1: Pretreatment of Zirconium-Containing Titanium Dioxide Raw Material. The zirconium-containing titanium dioxide raw material is crushed and ground to achieve a particle size within a predetermined range. The original zirconium content of the zirconium-containing titanium dioxide raw material is 0.1 wt% to 5 wt%, and the particle size D50 of the ground material is 0.5 to 10 μm. During the pretreatment process, the raw material is first initially crushed by a jaw crusher to pulverize the lumpy raw material into coarse particles with a particle size of less than 5 mm; then, it is finely ground using an air jet mill or a wet ball mill. Alumina balls or zirconium beads are used as the grinding media, and the grinding time is set according to the initial particle size and target D50 value of the raw material, usually controlled within the range of 30 to 120 minutes. In the wet ball milling process, the solid content is controlled at 40% to 60 wt%, and the grinding media filling rate is 70% to 85%. After grinding, the particle size distribution of the product is detected by a laser particle size analyzer (such as the Malvern Mastersizer series) to ensure that the D50 value meets the requirement of 0.5 to 10 μm. After fine grinding, the specific surface area of the raw material increases significantly, providing the necessary geometric conditions for sufficient contact between the leaching agent and the zirconium impurity particles. During the grinding process, the lattice defects and fresh exposed surfaces on the surface of the titanium dioxide particles increase, which facilitates the diffusion of fluoride ions to the zirconium impurity phase interface and the occurrence of selective complexation reactions. The ground slurry is then spray-dried or vacuum-dried at 80°C to obtain a loose, powdery intermediate product for later use.
[0041] Step 2: Preparation of the selective leaching agent. The selective leaching agent is prepared by mixing a fluoride ion source with sulfuric acid in deionized water. The leaching agent is a mixed solution composed of a fluoride ion source, sulfuric acid, and deionized water, wherein the total fluoride ion concentration is 0.5 to 3 mol / L, and the sulfuric acid concentration is 1 to 4 mol / L. The fluoride ion source is at least one of fluorosilicic acid, ammonium bifluoride, ammonium fluoride, and sodium fluoride. During preparation, first, a calculated amount of deionized water is added to the preparation tank, with the water temperature controlled at 20 to 25°C. Then, under stirring conditions, the required amount of fluoride ion source reagent is slowly added at a stirring speed of 200 to 400 rpm for at least 15 minutes to ensure that the fluoride ion source is fully dissolved and uniformly dispersed in the aqueous phase. Finally, concentrated sulfuric acid (98%) is slowly added under continuous stirring, with the addition rate controlled so that the solution temperature does not exceed 40°C to prevent local overheating and fluoride decomposition. After the acid addition is complete, stirring continues for 30 minutes to allow the solution system to reach a homogeneous and stable state. The prepared leachate should be used immediately or sealed in a polyethylene or polypropylene storage container to prevent fluoride ions from escaping in gaseous form.
[0042] In a preferred embodiment of this step, the fluoride ion source is a mixture of fluorosilicic acid and ammonium bifluoride, with a molar ratio of 1:0.5 to 2. The introduction of fluorosilicic acid (H₂SiF₆) can provide SiF₆ in the leaching solution. 2- The complex ion undergoes partial hydrolysis in aqueous solution to form SiF5(OH). - Hydroxyfluorosilicate ions such as SiF4(OH)2 and free F - Fluorosilicic acid ions provide various forms of fluorine ligands for the complexation leaching of zirconium. Simultaneously, the silicate ions introduced by fluorosilicic acid can form co-precipitates with zirconium in subsequent neutralization and precipitation steps, facilitating the comprehensive recovery of zirconium and silicon and significantly improving the economics and resource utilization of the process. Ammonium bifluoride (NH4HF2) dissociates into NH4+ in solution. + F - And HF molecules, which can directly participate in the surface etching reaction of zirconium. When fluorosilicic acid and ammonium bifluoride are used in a molar ratio of 1:0.5 to 2, the fluorine ligand morphology distribution in the leaching system is more reasonable: ZrF6 with high stability constant. 2- Complex ions became the dominant species, while free F - Maintaining the concentration at an appropriate level ensures efficient leaching of zirconium while effectively inhibiting excessive dissolution of the titanium dioxide matrix, thereby achieving the goal of selective zirconium removal.
[0043] As another preferred embodiment of this step, the sulfuric acid concentration in step 2 is 2 to 3 mol / L, and the total fluoride ion concentration is 1 to 2 mol / L. Within this concentration range, the leaching rate of zirconium reaches its optimal value, and the dissolution loss of titanium dioxide under these conditions can be controlled within 1.5%, thus balancing the two key indicators of zirconium removal efficiency and titanium recovery rate. The lower limit of the sulfuric acid concentration is set at 1 mol / L to ensure sufficient acidity in the solution to suppress the amphoteric dissolution tendency of TiO2; the upper limit is set at 4 mol / L to avoid excessive acidity leading to a decrease in the stability of the fluorosilicic acid complex. When the sulfuric acid concentration exceeds 4 mol / L, the H+ in the solution... + Too high a concentration will react with ZrF6. 2- The competitive relationship between complex ions reduces the stability of zirconium-fluorine complexes. When the sulfuric acid concentration is below 1 mol / L, the solubility of TiO2 in fluorine-containing systems increases, leading to a higher titanium loss rate. The lower limit of fluoride ion concentration, 0.5 mol / L, is set based on the formation of a sufficient concentration of zirconium-fluorine complexes to ensure leaching efficiency; the upper limit of 3 mol / L is based on a comprehensive consideration of preventing excessive free F⁻ concentration from causing significant corrosion of the TiO2 matrix and operational safety.
[0044] Step 3: Selective complexation leaching. The pretreated titanium dioxide powder and the leaching agent prepared in Step 2 are added to the reaction vessel at a liquid-to-solid mass ratio of 3:1 to 10:1. The leaching reaction is carried out at 50 to 95°C for 0.5 to 5 hours under stirring, allowing zirconium to form soluble fluorine-zirconium complex ions that enter the liquid phase, while the titanium dioxide matrix remains in the solid phase. The method for determining the reaction endpoint is as follows:
[0045] (1) Zirconium concentration method in filtrate (preferred): Every 30 minutes, approximately 5 mL of slurry sample is taken from the sampling port of the reactor. After filtration through a 0.45 μm filter membrane, the Zr concentration in the filtrate is determined using an inductively coupled plasma optical emission spectrometer (ICP-OES). The leaching endpoint is determined when the difference between two consecutive measurements of the zirconium concentration in the filtrate is <5% and the zirconium concentration in the filtrate is <50 mg / L. It should be noted that the 50 mg / L threshold is applicable to conventional operating conditions where the initial zirconium content is in the range of 0.1~5 wt% and the liquid-solid ratio is in the range of 3:1~10:1. When the liquid-solid ratio is too high (e.g., >8:1) or the initial zirconium content is too low (<0.5 wt%), the endpoint zirconium concentration in the filtrate can be correspondingly relaxed to <80 mg / L. Specifically, the threshold is determined when the difference between two consecutive measurements is <5% and the zirconium concentration in the filtrate tends to stabilize. Those skilled in the art can make adaptive adjustments according to actual operating conditions.
[0046] (2) pH value method (auxiliary): Monitor the pH value change of the slurry in the reactor. When the pH value tends to stabilize (change rate < 0.1 pH unit / 10 minutes) and is close to the initial pH value (±0.3), it indicates that the zirconium has been basically leached.
[0047] (3) Dynamic adjustment logic: When the initial zirconium content of the raw material is ≥3 wt% or D50>5 μm, the leaching time is extended to 2.5~5 hours, and the temperature is maintained in the range of 75~85℃; when the zirconium content is <1 wt% and D50<2 μm, the leaching time can be shortened to 0.5~1.5 hours. When the filtrate zirconium concentration method is used to determine the endpoint, the actual leaching time is based on the arrival of the endpoint, and the time window is only used as a reference range.
[0048] The leaching reaction is carried out in a corrosion-resistant metal reactor equipped with an anchor-type agitator. The leaching system of this invention contains a high concentration of fluoride ions (F). - The leaching system contains 0.5–3 mol / L sulfuric acid and 1–4 mol / L sulfuric acid, both highly corrosive media. The leaching reaction must be carried out in a metal reactor resistant to HF corrosion. Specific materials include Hastelloy C-276, Monel alloy, titanium (TA2 / TA10), or a PTFE-lined steel reactor. A glass-lined tank can be used to store and prepare HF-free auxiliary solutions, but the reactor must not be made of silicate materials (such as glass-lined, ceramic, or glass). The leaching system in this application contains a high concentration of fluoride ions (F...). - Both HF (concentrations of 0.5~3 mol / L) and sulfuric acid (1~4 mol / L) are highly corrosive media. The main component of the glass / ceramic enamel is SiO2, which reacts violently with HF: SiO2 + 4HF → SiF4↑ + 2H2O. This reaction causes rapid corrosion and perforation of the enamel layer, leaching of silicon impurities that contaminate the product, and the generation of highly toxic SiF4 gas, posing a significant safety hazard. Recommended reactor materials are as follows:
[0049]
[0050] Given the risk of HF volatilization, the following safety facilities should be installed in the reaction area:
[0051] Gas monitoring and alarm: An HF gas detection probe is installed above the reactor, with an alarm threshold of 2 mg / m³. 3 ;
[0052] Tail gas absorption device: Tail gas that cannot be recovered after condensation and reflux is treated by an alkaline solution (NaOH 0.5-1 mol / L) absorption tower;
[0053] Forced ventilation system: air exchange rate ≥ 10 times / hour;
[0054] Personal protective equipment: Operators are equipped with HF-resistant face masks (calcium fluoride coated filter media) and protective gloves. The processing area is equipped with rinsing facilities and calcium gluconate gel first aid supplies.
[0055] The reactor jacket is heated by introducing heat transfer oil or steam at a rate controlled at 1 to 3 °C / min. The leaching temperature is controlled at 50 to 95 °C, and the leaching time is 0.5 to 5 hours.
[0056] The effect of temperature on zirconium removal efficiency is as follows:
[0057] When the leaching temperature is 50℃, the zirconium removal rate is about 70-75%. Even if the leaching time is extended to 5 hours, the zirconium removal effect is still difficult to meet the requirements for deep zirconium removal. At this time, the reaction activation energy is insufficient, and the collision frequency between fluoride ions and zirconium impurities is low, resulting in a low zirconium removal rate.
[0058] When the leaching temperature is 60℃, the zirconium removal rate is about 85%, and the leaching time needs to be extended to 4 hours to achieve a removal rate of more than 90%.
[0059] When the leaching temperature is 70℃, the zirconium removal rate can reach 92-94%, and the leaching time of 2 hours is sufficient to meet the requirements;
[0060] When the leaching temperature is 75-80℃, the zirconium removal rate and titanium selectivity reach the optimal balance, with the zirconium removal rate reaching over 95% and the titanium loss rate being less than 1.5%.
[0061] When the leaching temperature is 85℃, the zirconium removal rate can reach over 96%, but the titanium loss rate begins to rise to 2-2.5%.
[0062] When the leaching temperature is 95℃, the zirconium removal rate is close to 98%, but at this temperature, HF volatilization intensifies, the risk of equipment corrosion increases, and the titanium loss rate rises significantly to 3-4%.
[0063] Taking into account zirconium removal efficiency, titanium recovery rate, energy consumption and operational safety, this application preferably uses a leaching temperature of 70 to 85°C and a leaching time of 1 to 2.5 hours.
[0064] The core mechanism of the leaching reaction lies in the selective complexation between zirconium and fluoride ions. In sulfuric acid medium, zirconium exists as a tetravalent cation, which reacts with F... - The coordination ability is much stronger than that with SO4. 2- The coordination ability of zirconium-containing titanium dioxide particles. When zirconium-containing titanium dioxide particles come into contact with the leaching agent, fluoride ions in the solution first diffuse to the surface of the zirconium impurity phase and undergo an interfacial chemical reaction with the solid zirconium. The chemical equation for this reaction can be expressed as follows, and the core reaction for the dissolution of zirconium impurities from the solid phase to the liquid phase can be expressed as:
[0065] (Equation 1);
[0066]
[0067] - + ZrF6 2- (Equation 2);
[0068]
[0069] β6 ZrF6 2- 4+ - 6
[0070] The cumulative stability constant β6 of the hexafluorozirconium complex ion is approximately 10. 20 Up to 10 23 In contrast, Ti 4+ and - The complexation constant (β6 approximately 10) 8 Up to 10 10 (orders of magnitude) than Zr 4+ The corresponding value is 10 lower 12 Up to 10 15 This thermodynamic difference, which is twice that of the target complex, forms the chemical basis for selective complexation and separation.
[0071] Zirconium exists in zirconium-containing titanium dioxide raw materials mainly in two forms: (1) independent zirconium oxide (ZrO2) phase or zirconium silicate phase, existing as inclusions between TiO2 particles; (2) replacing Ti in an isomorphous form. 4+ Zirconium enters the TiO2 lattice, forming a limited Ti-Zr solid solution. Both of these occurrence states of zirconium can be selectively dissolved by a fluorinated sulfuric acid system—for the free zirconium oxide phase, fluoride ions directly attack the solid surface; for zirconium inside the lattice, fluoride ions must first diffuse to lattice defects to undergo a substitution reaction.
[0072] Under the leaching conditions described in this application (sulfuric acid 1~4 mol / L, fluoride ion 0.5~3 mol / L, temperature 50~95℃), zirconium mainly exists as ZrF6. 2- ZrF5 - Complex ions such as ZrF4 exist, and their distribution ratio can be calculated using Equation 3:
[0073] (Equation 3)
[0074] Where β1~β5 are the successive stability constants, and α0 is the mole fraction of the hexafluorozirconium complex ion.
[0075] As a preferred embodiment of this step, the original zirconium content of the zirconium-containing titanium dioxide raw material in step 3 is 0.1 wt% to 5 wt%, the raw material particle size D50 is 0.5 to 10 μm, and the liquid-solid mass ratio is 3:1 to 10:1. When the liquid-solid ratio is lower than 3:1, the viscosity of the leaching system is high, the stirring efficiency and mass transfer coefficient decrease, resulting in uneven reaction and reduced zirconium removal efficiency. When the liquid-solid ratio is higher than 10:1, although the reaction environment is improved, the equipment utilization rate decreases, the reagent consumption and energy consumption per unit mass of raw material processed increase, and the economic efficiency deteriorates. The optimal liquid-solid ratio range is 5:1 to 8:1, at which point the fluidity and mass transfer efficiency of the leaching system are at their optimal state, and the zirconium leaching kinetics curve tends to be complete within a given time.
[0076] Step 4: Solid-Liquid Separation and Product Preparation. After the leaching reaction is completed, the leaching slurry undergoes solid-liquid separation. The resulting filter cake is washed with deionized water until the pH of the washing solution is close to neutral. The filter cake is then dried at 100 to 150°C to obtain the low-zirconium titanium dioxide product. Solid-liquid separation is performed using vacuum filtration or pressure filtration. Vacuum filtration uses a Buchner funnel with a circulating water vacuum pump, and the vacuum level is controlled at -0.08 to -0.09 MPa. Pressure filtration uses a plate and frame filter press or a diaphragm filter press, and the working pressure is controlled at 0.4 to 0.6 MPa. The filter cloth is made of corrosion-resistant polypropylene with a pore size of 1 to 5 μm. During filtration, the slurry temperature is maintained within the range of 60 to 80°C to prevent crystallization blockage caused by temperature drop. The filter cake is washed with deionized water at a washing temperature of 60 to 80°C. The liquid-to-solid ratio is controlled at 2:1 to 3:1 for each wash, and the number of washes is 2 to 4. The washing endpoint is determined by measuring the pH and conductivity of the washing solution: when the pH of the washing solution reaches the range of 6.5 to 7.5 and the conductivity is below 50 μS / cm, it indicates that the residual sulfate and fluoride ions in the filter cake have been fully washed away. This operation effectively removes residual sulfate and fluoride ions from the filter cake, avoiding the formation of insoluble salts (such as calcium fluoride, calcium sulfate, etc.) during the drying process, which would affect the purity of the product. The washed filter cake is dried at 100 to 150°C. The drying time is determined according to the moisture content of the filter cake and the type of drying equipment, usually 2 to 6 hours. Drying equipment can include an oven, a fluidized bed dryer, or a spray drying tower. The dried low-zirconium titanium dioxide product is then ground and sieved (usually with a mesh size of 200 to 325 mesh) to obtain a final product with uniform particle size. The zirconium content in the product is less than 0.05 wt%, and the titanium recovery rate is greater than 98.5%.
[0077] Step 5: Leachate Treatment and Recycling. An alkaline substance is added to the leachate after solid-liquid separation to adjust the pH to 8-10, causing zirconium and residual impurities to precipitate. The supernatant, after composition adjustment, is returned for use in preparing the leaching agent. The performance maintenance method for recycling is as follows:
[0078] (1) Batch Circulation Control: The leaching agent can be recycled for 5-10 batches, with the specific number of cycles depending on the impurity content in the raw material. When Fe is detected in the supernatant... 3+ Concentration >2 g / L, Al 3+ Concentration >1 g / L or Ca 2+ When the concentration is >3 g / L, a portion of the leaching agent (not less than 20% of the total amount) should be discharged and replaced with freshly prepared leaching agent to maintain the selectivity of the system.
[0079] (2) Fluoride ion concentration maintenance: Before each batch cycle, free F is measured by an online fluoride ion selective electrode. - Concentration. When free F - When the concentration is below 80% of the initial value, add a calculated amount of fluorosilicic acid or ammonium bifluoride to bring it back to the original concentration level. The amount added is calculated as Δ[F]. - ] × Calculation of total amount of leachate.
[0080] (3) Impurity removal method: When the accumulation of impurity ions leads to a decrease in selectivity, lime milk (Ca(OH)2 concentration 10~15 wt%) is used to adjust the pH to 10~11, so that Fe 3+ Al 3+ Removed by the formation of hydroxide precipitate, Ca 2+ The sample was separated by precipitation in the form of calcium sulfate; after precipitation, the supernatant was replenished with a fluoride ion source and sulfuric acid to restore it to its original composition.
[0081] (4) Judgment of the end point of recycling: When the titanium recovery rate of two consecutive batches of products is less than 97% or the zirconium content is higher than 0.06 wt%, recycling should be stopped and the leaching agent should be regenerated or completely replaced.
[0082] Step 5 is optional, but it is of great significance in terms of resource utilization and environmental protection. The alkaline substance added to the leachate can be any one of lime milk, sodium hydroxide, or calcium hydroxide. In practice, the alkaline substance is prepared into a 5% to 15% solution and slowly added dropwise to the leachate under continuous stirring, with the addition rate controlled so that the pH change rate does not exceed 0.5 units / minute. When the pH is adjusted to 8.5 to 9.5, the zirconium precipitation rate can reach over 95%. Under alkaline conditions, zirconium precipitates as hydroxides or fluoride oxides. Simultaneously, silicate ions in the solution (derived from the hydrolysis of fluorosilicic acid) co-precipitate with the zirconium, forming a zirconium-silicon slag mixture. This precipitate product, after pressure filtration and drying, can be sold or further processed as zirconium-silicon slag, achieving resource utilization of by-products. Pressure filtration uses a plate and frame filter press, and the filter cake is dried at 100 to 120°C for 4 to 8 hours to obtain a zirconium-silicon slag product containing 15% to 30% zirconium. After compositional analysis, the supernatant is replenished with calculated amounts of fluoride ion source and sulfuric acid to restore the leaching agent composition to the requirements of step 2. It is then returned to prepare new leaching agents, achieving the recycling of the process system. During recycling, key indicators such as fluoride ion concentration, sulfuric acid concentration, and iron ion concentration in the supernatant are analyzed and monitored for each batch to ensure that recycling does not affect zirconium removal efficiency and product quality.
[0083] A specific application example. Titanium dioxide, obtained by calcining metatitanic acid produced by the sulfuric acid process at 900℃, was used as raw material. Its TiO2 content was 98.2%, and its Zr content was 1.8 wt%. The raw material was ground to D50 = 2.5 μm using a wet ball mill with zirconium oxide beads as the milling media. The milling speed was 400 rpm, and the milling time was 60 minutes, resulting in a slurry solid content of 50 wt%. After grinding, the slurry was spray-dried to obtain a loose powder for later use. The process for preparing the leaching agent was as follows: 250 L of deionized water (22℃) was added to a 500 L glass-lined preparation tank. The anchor stirrer was turned on at 300 rpm. 67.2 kg of 40% concentration fluorosilicic acid (H2SiF6) and 68.0 kg of 98% concentrated sulfuric acid were added sequentially, controlling the temperature to not exceed 38℃ during acid addition. After acid addition, stirring was continued for 30 minutes to ensure a uniform and stable solution. The final leaching agent contained 0.8 mol / L H₂SiF₆, equivalent to a total fluoride ion concentration of approximately 2.4 mol / L. However, due to the SiF₆... 2- Partial hydrolysis occurs, and the available free fluorine is provided by the hydrolysis equilibrium; the sulfuric acid concentration is 2.5 mol / L.
[0084] The selective complexation leaching process is as follows: 100 kg of ground titanium dioxide powder and 600 L of leaching agent are added to a 2000 L Hastelloy C-276 reactor (or a PTFE-lined steel reactor). Anchor stirring is started at 300 rpm. The temperature is raised to 80°C via jacketed heat transfer oil at a rate of 2°C / min. After reaching 80°C, leaching is carried out at this temperature for 2 hours, maintaining constant stirring and temperature. After the leaching reaction is completed, vacuum filtration is performed while hot, with a vacuum degree of -0.085 MPa. The filtrate temperature is maintained above 70°C to prevent crystallization. The filter cake is washed three times countercurrently with 80°C deionized water, with 200 L of washing liquid used each time. The pH of the washing liquid is gradually increased from the initial 1.5 to 7.2. After washing, the filter cake is dried at 120°C for 4 hours to obtain the dried filter cake product. The dried product is then sieved through a 200-mesh sieve to obtain the final low-zirconium titanium dioxide product. The product was analyzed by inductively coupled plasma optical emission spectrometry (ICP-OES), showing a Zr content of 0.028 wt% and a TiO2 content of 99.4%, with a calculated titanium recovery rate of 99.2%. The leachate (approximately 550 L) was adjusted to pH 9 by adding lime milk (containing 12% CaO), with approximately 18 L of lime milk added. After a precipitation reaction of 30 minutes, the solution was filtered to obtain approximately 8.5 kg of filter cake. The dried filter cake was a grayish-white powder, and X-ray fluorescence spectrometry (XRF) analysis revealed its composition to be 22.5% ZrO2, 31.2% SiO2, 18.6% CaO, 6.8% TiO2, and other impurities. This powder can be sold as a zirconium-silicon resource. The supernatant showed a fluoride ion concentration that decreased to 0.08 mol / L. After adding fluorosilicic acid and sulfuric acid to restore the initial concentration, the supernatant was returned for use in preparing new batches of leachate.
[0085] An HF gas detection probe (alarm threshold 2 mg / m³) is installed above the reaction area, and an alkaline solution (NaOH 0.5~1mol / L) absorption tower is used to treat the tail gas.
[0086] Example 2
[0087] This embodiment uses titanium dioxide fine powder obtained from chlorination post-treatment as raw material to verify the adaptability of the process of the present invention to zirconium-containing titanium dioxide raw materials from different sources.
[0088] The raw material is fine titanium dioxide powder collected during the dust collection process of the chloride oxidation stage, with a TiO2 content of 97.5%, a Zr content of 2.3 wt%, and a raw material D50 of 1.8 μm. Due to its fine particle size, no additional grinding is required, and it can be directly used in the leaching step. The leaching agent composition is: 0.6 mol / L fluorosilicic acid (H2SiF6), 0.6 mol / L ammonium bifluoride (NH4HF2), and 2.8 mol / L sulfuric acid. In this leaching agent formulation, the molar ratio of fluorosilicic acid to ammonium bifluoride is 1:1, which is in the middle of the preferred range of 1:0.5 to 2. The combined use of two fluoride ion sources enriches the fluorine ligand morphology in the solution, particularly SiF6. 2- HF and F - The synergistic effect of these factors is beneficial to improving the leaching rate and selectivity of zirconium.
[0089] In the selective complexation leaching process, the liquid-to-solid mass ratio was 8:1, the leaching temperature was 85℃, and the leaching time was 2.5 hours. The higher leaching temperature (85℃) is beneficial for accelerating reaction kinetics, but at the same time, it is necessary to strengthen the protection against HF volatilization. A reflux condenser was installed above the reactor to condense and reflux the volatilized fluorine-containing gas back into the reaction system. After leaching, vacuum filtration was performed, and the filter cake was washed three times with 70℃ deionized water until the pH reached 7.0, and then dried at 130℃ for 5 hours to obtain the final product.
[0090] The product testing results were: Zr content 0.019 wt%, TiO2 content 99.5%, and titanium recovery rate 98.7%. The results of this example indicate that when the zirconium content in the raw material is high (2.3 wt%) and the particle size is fine, the composite fluoride ion source system using fluorosilicic acid and ammonium bifluoride can achieve a deeper zirconium removal effect within a moderately extended leaching time (2.5 hours), reducing the zirconium content in the product to below 0.02 wt%, significantly better than the results of Example 1. The reasons for this are twofold: firstly, the finer particle size of the raw material (D50 1.8 μm vs 2.5 μm) increases the specific surface area, which is beneficial for leaching mass transfer; secondly, the composite fluoride ion source system provides more forms of fluorine ligands, enhancing the driving force for zirconium complexation leaching.
[0091] Example 3
[0092] This embodiment uses titanium dioxide enrichment obtained by alkaline melting and acid leaching of low-grade titanium slag as raw material to verify the ability of the process of the present invention to process raw materials with high impurity content.
[0093] The raw material is a titanium dioxide enrichment obtained from low-grade titanium slag through alkali fusion and acid leaching. Its TiO2 content is 92.1%, Zr content is 3.5 wt%, and it also contains approximately 3.2 wt% silicon impurities and 1.1 wt% iron impurities. Due to the low TiO2 content and high impurity content of this raw material, deep zirconium removal treatment is required to upgrade the product grade to electronic-grade requirements. Because the raw material has a relatively coarse particle size (D50 approximately 15 μm), it is first ground to D50 = 5 μm using wet ball milling with stainless steel beads as the milling media for 90 minutes.
[0094] The leaching agent consisted of 2.0 mol / L ammonium fluoride (NH4F) and 3.5 mol / L sulfuric acid. Using ammonium fluoride as the sole fluoride ion source simplified the leaching agent preparation process and reduced the complexity of reagent procurement and storage. The higher sulfuric acid concentration (3.5 mol / L) helped maintain the system's acidity in a high-impurity environment and inhibited the non-selective dissolution of impurities. The liquid-to-solid mass ratio was 10:1, the leaching temperature was 90℃, and the leaching time was 3 hours.
[0095] After solid-liquid separation, the filter cake is washed four times with deionized water until the pH reaches 6.8, and then rinsed with hot deionized water at 80°C for the last time to remove residual fluoride ions. The filter cake is then dried at 140°C for 6 hours to obtain the final product.
[0096] The product testing results are as follows: Zr content 0.041 wt%, TiO2 content 96.8%, and titanium recovery rate 97.8%. It should be noted that the titanium recovery rate in this embodiment is slightly lower than 98.5% due to the extremely high impurity content in the raw material (total impurities nearly 8 wt%). Some ultrafine titanium particles inevitably suffer mechanical entrainment loss during multiple washing processes, and trace amounts of titanium dissolve under high acidity conditions. However, in actual industrial applications, the titanium recovery rate can be increased to over 98.5% by optimizing the washing process (such as using cross-flow filtration or ceramic membrane filtration). This embodiment serves as verification data under extreme conditions, demonstrating that the process of this invention can still achieve the core objective of a zirconium content below 0.05 wt% even with high-impurity raw materials. The silicon content in the product decreased from 3.2 wt% in the raw material to 0.8 wt%, and the iron content decreased from 1.1 wt% to 0.3 wt%, indicating that in the fluorinated sulfuric acid system, associated impurities such as silicon and iron were also partially removed, further improving the overall purity of the product. This embodiment demonstrates that even for titanium slag enrichment products with complex composition and high impurity content, the process of the present invention can still achieve the goal of reducing the zirconium content to below 0.05 wt% while maintaining an acceptable titanium recovery rate.
[0097] Example 4
[0098] A calcined metatitanic acid product with a zirconium content of 2.1 wt% (same raw material batch as in Example 1) was used for verification experiments under low-temperature (55℃, leaching for 5 hours) and high-temperature (92℃, leaching for 1 hour) conditions. The results showed that under low-temperature conditions, the zirconium content decreased to 0.28 wt% (zirconium removal rate 86.5%), and the titanium recovery rate was 99.2%; under high-temperature conditions, the zirconium content decreased to 0.048 wt% (zirconium removal rate 97.7%), but the titanium recovery rate decreased to 96.8%. These data verified the technical effectiveness within the parameter boundary range, indicating that the process of this invention still has a certain zirconium removal capability outside the preferred temperature range (70~85℃), but considering the overall titanium recovery rate, the preferred temperature range has greater industrial application value.
[0099] Comparative Example 1 (Fluoride-free control)
[0100] The leaching agent contained only 2.5 mol / L sulfuric acid, without any fluoride ion source, with a liquid-to-solid ratio of 6:1, a leaching temperature of 80℃, and a leaching time of 2 hours. The raw material was the same as in Example 1. After treatment, the Zr content of the product was still as high as 1.4 wt%, a decrease of only 22% compared to the 1.8 wt% of the raw material, far from meeting the requirements for deep zirconium removal. This result indicates that in a simple sulfuric acid system without fluoride ions, zirconium impurities hardly dissolve. The acidity of sulfuric acid alone cannot destroy the stable structure of the zirconium-bearing mineral phase; zirconium removal must rely on the complexation and coordination of fluoride ions.
[0101] Comparative Example 2 (Direct Leaching with Hydrofluoric Acid)
[0102] A mixed solution containing 1.0 mol / L HF and 1.0 mol / L H2SO4 was used as the leaching agent, and leaching was carried out at 80°C for 2 hours with a liquid-to-solid ratio of 6:1 to treat the raw material in Example 1. Although the Zr content could be reduced to below 0.042 wt% under these conditions, the titanium recovery rate was only 85.3%, and the titanium loss rate was as high as 14.7%. In addition, HF volatilization was severe during the operation, and the HF concentration detected above the reactor exceeded the occupational exposure limit (2 mg / m³), requiring the installation of a complete ventilation and gas absorption system. This not only increased equipment investment but also posed a threat to the occupational health and safety of the operators.
[0103] The experimental data from Comparative Examples 1 and 2 confirm that this invention, by precisely controlling the ratio of fluoride ion concentration (0.5 to 3 mol / L) and sulfuric acid concentration (1 to 4 mol / L), achieves deep zirconium removal while keeping the titanium loss rate below 2%. It takes into account multiple requirements such as zirconium removal efficiency, titanium recovery rate, operational safety, and environmental friendliness, and is a new selective complexation leaching process with excellent comprehensive performance.
[0104] Comparative experimental data confirm that this invention, by precisely controlling the ratio of fluoride ion concentration (0.5 to 3 mol / L) and sulfuric acid concentration (1 to 4 mol / L), achieves deep zirconium removal while keeping titanium loss rate below 2%. It takes into account multiple requirements such as zirconium removal efficiency, titanium recovery rate, operational safety, and environmental friendliness, and is a new selective complexation leaching process with excellent comprehensive performance.
[0105] The reaction mechanism of this invention is further explained below. In an aqueous solution of fluorinated sulfuric acid, the complexation reaction between fluoride ions and zirconium ions is a multi-step, stepwise coordination process. Various fluoride-zirconium complex ion forms exist in the solution, including ZrF... + ZrF2 2 + ZrF3 + ZrF4, ZrF5 - and ZrF6 2- The distribution ratio of these components depends on the fluoride ion concentration and the acidity of the solution. Under the process conditions set in this invention (total fluoride concentration 0.5 to 3 mol / L, sulfuric acid concentration 1 to 4 mol / L), ZrF6 2- and ZrF5 - It is the dominant species because of its high fluorine-to-zirconium ratio (F). - / Zr 4+ This favors the formation of complexes with high coordination numbers. The equilibrium relationship of this complexation reaction can be described by the following expression:
[0106]
[0107] The cumulative stability constant β6 of the hexafluorozirconium complex ion is approximately 10. 20 Up to 10 23 Order of magnitude higher than the complexation constant (β) between zirconium and sulfate. s Approximately 10 3 The order of magnitude of the fluoride ion's coordination selectivity with zirconium fundamentally determines this. The ultra-high stability of the zirconium-fluoride complex provides a strong thermodynamic driving force for the dissolution reaction of solid-phase zirconium, allowing it to proceed rapidly even under moderate temperature conditions. In contrast, Ti... 4+ With F - The complexation constant (β6 approximately 10) 8 Up to 10 10 (orders of magnitude) than Zr 4+ The corresponding value is 10 lower 12 Up to 10 15 Therefore, in the same fluorinated sulfuric acid system, Ti 4+Almost no significant complexation-dissolution reaction occurs. This significant thermodynamic difference is the fundamental reason why this invention achieves highly selective zirconium removal while maintaining high titanium recovery. Furthermore, the presence of high-concentration sulfuric acid (1 to 4 mol / L) further suppresses TiO2 dissolution: high H... + Concentration inhibited the formation of negatively charged regions on the TiO2 surface, reducing its amphoteric dissolution tendency; meanwhile, SO4 2- With Ti 4+ The weak complex formed occupies Ti 4+ Some of the coordination sites reduce the likelihood of further coordination with F⁻.
[0108] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the technical solution of the present invention is not limited to the description of the specific embodiments above. Any modifications, equivalent substitutions, or improvements made without departing from the spirit and scope of the present invention should be included within the protection scope of the present invention. The selective complexation leaching process claimed in this invention achieves highly selective deep zirconium removal from zirconium-containing titanium dioxide raw materials under mild conditions by precisely controlling key process parameters such as fluoride ion concentration, sulfuric acid concentration, leaching temperature, leaching time, and liquid-solid ratio, utilizing the chemical principle of zirconium reacting with fluoride ions to form a highly stable hexafluorozirconium complex. This process ensures zirconium removal efficiency while controlling the titanium loss rate to a low level, and the leachate can be recycled. The process operation is safe and environmentally friendly, and it is suitable for deep zirconium removal from various industrial raw materials such as calcined products of the sulfuric acid process, dust collected during the oxidation stage of the chloride process, and titanium dioxide enriched in titanium slag, showing broad application prospects.
Claims
1. A selective complexation leaching process for deep zirconium removal from electronic-grade titanium dioxide, characterized in that, Includes the following steps: Step 1: Pre-treat the zirconium-containing titanium dioxide raw material by crushing and grinding the raw material to a particle size D50 of 0.5 to 10 μm to obtain pre-treated titanium dioxide powder. Step 2: Prepare a selective leaching agent by mixing a fluoride ion source with sulfuric acid in deionized water. The total fluoride ion concentration in the leaching agent is 0.5 to 3 mol / L, and the sulfuric acid concentration is 1 to 4 mol / L. Step 3: The pretreated titanium dioxide powder is mixed with the leaching agent prepared in Step 2 at a liquid-solid mass ratio of 3:1 to 10:
1. A selective complexation leaching reaction is carried out at 50 to 95°C for 0.5 to 5 hours under stirring conditions, allowing zirconium to form soluble fluorine-zirconium complex ions that enter the liquid phase. These fluorine-zirconium complex ions include at least the zirconium hexafluorophosphate complex ion ZrF6. 2- The titanium dioxide matrix remains in a solid state. The reaction endpoint is determined by the zirconium concentration method in the filtrate. The leaching endpoint is defined as follows: when the difference in Zr concentration between two consecutive samples is <5% and the Zr concentration in the filtrate is <50 mg / L (this can be relaxed to <80 mg / L if the liquid-to-solid ratio is >8:1 or the initial zirconium content is <0.5 wt%); or the pH value can be used as an auxiliary method. The leaching endpoint is defined as follows: when the pH change rate of the slurry is <0.1 pH unit / 10 minutes and is close to the initial pH value ±0.
3. Step 4: The slurry after leaching reaction is subjected to solid-liquid separation. The resulting filter cake is washed and dried to obtain a low-zirconium titanium dioxide product. Step 5: Add an alkaline substance to the leachate after solid-liquid separation to adjust the pH to 8 to 10, so that zirconium precipitates out. The supernatant is then returned to be used to prepare the leachate after the composition is adjusted.
2. The selective complexation leaching process according to claim 1, characterized in that, The grinding described in step 1 is performed using wet ball milling or air jet milling, with alumina balls or zirconium beads as the grinding media. In the wet ball milling process, the solid content is controlled at 40% to 60 wt%, and the grinding media filling rate is 70% to 85%.
3. The selective complexation leaching process according to claim 1, characterized in that, The slurry ground in step 1 is spray-dried or vacuum-dried at 80°C to obtain a loose, powdery intermediate product.
4. The selective complexation leaching process according to claim 1, characterized in that, The fluoride ion source mentioned in step 2 is at least one of fluorosilicic acid, ammonium bifluoride, ammonium fluoride, and sodium fluoride.
5. The selective complexation leaching process according to claim 1, characterized in that, The fluoride ion source mentioned in step 2 is a mixture of fluorosilicic acid and ammonium hydrogen fluoride, with a molar ratio of 1:0.5 to 2.
6. The selective complexation leaching process according to claim 1, characterized in that, In step 2, the sulfuric acid concentration is 2 to 3 mol / L, and the total fluoride ion concentration is 1 to 2 mol / L.
7. The selective complexation leaching process according to claim 1, characterized in that, The liquid-solid mass ratio in step 3 is 3:1 to 10:1, the leaching temperature is 70 to 85°C, and the leaching time is 1 to 2.5 hours.
8. The selective complexation leaching process according to claim 1, characterized in that, The liquid-solid mass ratio mentioned in step 3 is 5:1 to 8:
1.
9. The selective complexation leaching process according to claim 1, characterized in that, The solid-liquid separation in step 4 is performed by vacuum filtration or pressure filtration. The filter cake is washed with deionized water until the pH is 6.5 to 7.5 at a washing temperature of 60 to 80°C. The filter cake is dried at 100 to 150°C. After drying, the zirconium content in the product is less than 0.05 wt%, and the titanium recovery rate is not less than 97%.
10. A low-zirconium titanium dioxide product, characterized in that, The low-zirconium titanium dioxide product is prepared by the selective complexation leaching process according to any one of claims 1 to 9, wherein the zirconium content is less than 0.05 wt% and the titanium recovery rate is not less than 97%.
Citation Information
Patent Citations
A method for preparing high-purity electronic-grade titanium dioxide from ilmenite
CN120350251B
Process for preparing high-purity zirconium dioxide
CN1594104A
